2008
DOI: 10.1002/jrs.1854
|View full text |Cite
|
Sign up to set email alerts
|

A Raman spectroscopic and combined analytical approach to the restoration of severely damaged frescoes: the Palomino project

Abstract: The deterioration of art objects is normally relatively minor, controllable and attributable to environmental changes or bacterial invasion, and until now there has not been any recorded attempt to analyse an artwork that has been deliberately and significantly destroyed. The analytical problems are correspondingly larger but the potential reward from any information that can be forthcoming is thereby proportionately greater. The 17th Century Palomino frescoes on the vaulted ceiling of the Church of Sant Joan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Differences between ancient and modern mortars are found. A Raman characterisation of painted mortar in Republican Raman mosaics was reported by Boschetti et al [43] A Raman spectroscopic and combined analytical (scanning electron microscopy and voltammetry of microparticles) approach to analyse the restoration of severely damaged 17th century Palomino frescoes on the vaulted ceiling of the Church of Sant Joan del Mercat in Valencia, Spain, was published by Edwards et al [44] Prinsloo et al [45] reported on the first Raman spectroscopic study of San rock art in the Ukhahlamba Drakensberg Park, South Africa. The authors have shown that Raman spectroscopy can play a very useful role in unravelling the key factors that contribute to the complex mechanism of weathering of the rock faces depicting San rock art.…”
Section: Frescos Mortars Paintings Including Wall and Rock Paintingmentioning
confidence: 99%
“…Differences between ancient and modern mortars are found. A Raman characterisation of painted mortar in Republican Raman mosaics was reported by Boschetti et al [43] A Raman spectroscopic and combined analytical (scanning electron microscopy and voltammetry of microparticles) approach to analyse the restoration of severely damaged 17th century Palomino frescoes on the vaulted ceiling of the Church of Sant Joan del Mercat in Valencia, Spain, was published by Edwards et al [44] Prinsloo et al [45] reported on the first Raman spectroscopic study of San rock art in the Ukhahlamba Drakensberg Park, South Africa. The authors have shown that Raman spectroscopy can play a very useful role in unravelling the key factors that contribute to the complex mechanism of weathering of the rock faces depicting San rock art.…”
Section: Frescos Mortars Paintings Including Wall and Rock Paintingmentioning
confidence: 99%
“…During this period, seven fires were lit in the church in an attempt to destroy the frescoes. Thus, the recognition of unusual alteration products formed from the pigments, as well as from substrate and ground layers, has been another important aim of the scientific study carried out on the frescoes at Sant Joan del Mercat along with the analytical identification of pigments and painting materials, a problem that has been partially solved in prior works …”
Section: Introductionmentioning
confidence: 99%
“…This question has been the subject of several scientific studies on the alteration of wall paintings and frescoes. [6,13,14] Pérez-Alonso et al have observed extensive damage in frescoes in the church of Santa Maria, located in the Monasterio de Hermo, Asturas. Visual and spectroscopic examinations were used to identify the percolation and upward migration of salts as the initial cause of damage, the nitrates of the salts being probably the migrant species from the old cemetery.…”
Section: Introductionmentioning
confidence: 99%